Molecular Phylogeny and Adaptive Mitochondrial DNA Evolution of Salmonids (Pisces: Salmonidae) - Wang, Ying; Xiong, Fei; Song, Zhaobin (Frontiers in Genetics, 2022)
Salmonids are comprised of anadromous and freshwater fishes, which is an important model for studying adaptive evolution. Herein, 49 salmonid complete mitochondrial genomes as well as those of two outgroups were used to infer a robust phylogeny for the family Salmonidae. The BI and RAxML phylogenetic trees based on 13 concatenated mitochondrial protein-coding genes showed well-supported nodes and topologies were highly congruent. The concatenated 13 mitochondrial protein-coding genes, ND2, ND3 and ND5 genes were shown to have significantly larger dN/dS ratios in anadromous species than in freshwater species of Salmonidae, but CYTB gene had a significantly smaller dN/dS in anadromous species. The FEL analysis identified positively selected sites and negatively selected sites in each mitochondrial protein-coding gene separately. The RELAX program revealed that the ATP8 and CYTB genes supported intensified selection on the anadromous lineages. Our results demonstrated the phylogeny of Salmonidae and explored the mitochondrial DNA evolution pattern between anadromous and freshwater salmonids.